Penerapan Alih Baring dan Pemberian Minyak Zaitun untuk Mencegah Gangguan Integritas Kulit pada Pasien Stroke Non Hemoragik: Studi Kasus di Ruang Stroke Unit RSD Gunung Jati Kota Cirebon 2026 - Jeesyca Vivi Lianti Nova Hermanto; Dewi Erna Marisa; Ahmad Syaripudin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Non-hemorrhagic Stroke often causes mobility impairment that increases the risk of impaired skin integrity and pressure ulcers due to prolonged bed rest. Repositioning and olive oil application are evidence-based nursing interventions that may help maintain skin integrity and prevent skin damage in immobilized patients. Objective: To determine the effectiveness of repositioning and olive oil application in preventing impaired skin integrity among patients with non-hemorrhagic Stroke. Methods: A case study was conducted on one patient with non-hemorrhagic Stroke who experienced impaired skin integrity in the Stroke Unit of Gunung Jati Regional Hospital, Cirebon City. Data were collected through interviews, observations, physical examinations, and documentation studies. Nursing interventions included repositioning every two hours and olive oil application to pressure-prone areas for three consecutive days. Results: The interventions resulted in decreased redness on bony prominence areas, improved skin moisture, and maintenance of intact skin integrity without signs of tissue damage or pressure ulcer development. Implications: Repositioning and olive oil application are effective nursing interventions for maintaining skin integrity and preventing pressure ulcers in non-hemorrhagic Stroke patients with limited mobility.